A comparative analysis of three different methods for the estimation of the basic reproduction number of dengue - Rosangela Peregrina Sanches; Eduardo Massad (Infectious Disease Modelling, 2016)
The basic reproduction number, R0, is defined as the expected number of secondary cases of a disease produced by a single infection in a completely susceptible population, and can be estimated in several ways. For example, from the stability analysis of a compartmental model; through the use of the matrix of next generation, or from the final size of an epidemic, etc. In this paper we applied the method for estimating R0 of dengue fever from the initial growth phase of an outbreak, without assuming exponential growth of cases, a common assumption in many studies. We used three different methods of calculating R0 to compare the techniques' details and to evaluate how these techniques estimate the value of R0 of dengue using data from the city of Ribeirão Preto (SE of Brazil) in two outbreaks. The results of the three methods are numerically different but, when we compare them using a system of differential equations developed for modeling only the first generation time, we can observe that the methods differ little in the initial growth phase. We conclude that the methods predict that dengue will spread in the city studied and the analysis of the data shows that the estimated values of R0 have an equal pattern overtime. Keywords: Basic reproduction number, Dengue, Mathematical models, Likelihood-based model